Development and Acceptability of Environmental Education Kit for Elementary Learners - Lura Love Castro; Windy Marie Cawayan; Chendy Maximino; Tomas Jr Diquito (Scientia Publica Media, 2025)
Contextualizing environmental education is a significant factor in shaping learners’ understanding of their environment. The absence of local knowledge in environmental education can significantly impact learners’ ability to understand environmental learning when applied in their local context. This study has developed an Environmental Education Kit (EE Kit) containing contextualized activities aligned with the learning competencies listed in the newly implemented MATATAG or K–10 Curriculum for elementary learners in Davao del Sur, Philippines. The use of developmental research design was employed in this study since the main goal of the study is to create a contextualized EE Kit. In developing the EE Kit, the researchers have included five components, namely, topics, specific objectives, key concepts, directions, and activities. To determine the appropriateness of the developed EE Kit, 44 elementary science teachers from the Province of Davao del Sur, Philippines, were invited to participate in this study. The questionnaire used involved a Likert scale with five response options to assess various aspects of the kit, including its language, format and layout, and level of difficulty. Result of the analysis shows that teachers have rated all indicators under the content and face validity components as highly acceptable, providing positive feedback on the EE Kit’s potential as a valuable resource to enhance contextualized learning in environmental education. Therefore, it is recommended that elementary science teachers utilize the EE Kit to allow hands-on experiences under the newly implemented curricula. Moreover, the need for future studies to assess the EE kit’s efficacy from the learners’ perspective is recommended, demonstrating our ongoing commitment to improving the EE Kit for Filipino learners.